Synthesis, Anti-microbial and Molecular Docking Studies of Quinazolin-4(3H)-one Derivatives - Yahia Nasser Mabkhot; Munirah S. Al-Har; Assem Barakat; Fahad D. Aldawsari; Ali Aldalbahi; Zaheer Ul-Haq (Molecules, 2014)
In this work, synthesis, antimicrobial activities and molecular docking studies of some new series of substituted quinazolinone 2a–h and 3a–d were described. Starting form 2-aminobenzamide derivatives 1, a new series of quinazolinone derivatives has been synthesized, in high yields, assisted by microwave and classical methods. Some of these substituted quinazolinones were tested for their antimicrobial activity against Gram-negative bacteria (Pseudomonas aeruginosa and Esherichia coli) and Gram-positive bacteria (Staphylococcus aureus, and Bacillus subtilis), and anti-fungal activity against (Aspergillus fumigatus, Saccharomyces cervevisiae, and Candida albicans) using agar well diffusion method. Among the prepared products, 3-benzyl-2-(4-chlorophenyl)quinazolin-4(3H)-one (3a) was found to exhibits the most potent in vitro anti-microbial activity with MICs of 25.6 ± 0.5, 24.3 ± 0.4, 30.1 ± 0.6, and 25.1 ± 0.5 µg/mL against Staphylococcus aureus, Bacillus subtilis, Pseudomonas aeruginosa and Esherichia coli, respectively. Compound 3a was found to exhibits the most potent in vitro anti-fungal activity with MICs of 18.3 ± 0.6, 23.1 ± 0.4, and 26.1 ± 0. 5 µg/mL against Aspergillus fumigatus, Saccharomyces cervevisiae, and Candidaal bicans, respectively.